PENGARUH EKONOMI MAKRO DALAM PERGERAKAN NILAI TUKAR RUPIAH - Pihri Buhaerah (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
This paper examines empirically the impact of key macroeconomic variables on Exchange rate Fluctuation in Indonesia for the period 200Q1-2015Q2by using error correction model (ECM)to achieve the objective of this study , data was collected from secondary sources and various econometric analysis such as unit root test, Engle and Granger cointegration test, error corection ( ECM) were employed. Engle and Granger conitegration test shows that there is along run relationship cointegration between certain key macroeconomic variables and nominal exchange rate. Error correction model shows that share prices index and external debt have significant effect on nominal exchange rate in the short-run. Interestingly, official reserve assets and oil price as well as share price index have negative realtionship with nominal exchange rate. In contrast, external debt and trade deficit affect rupiah against US Dollar positively. Therefore , Indonesian Fiscal, monetary, and financial authorities should be more focused on increasing share index and reducing external debt in the short-run rather than focusing on improving trade balance or increasing official reserve assets.